2009
DOI: 10.1021/ol802845w
|View full text |Cite
|
Sign up to set email alerts
|

Star-Shaped D-π-A Conjugated Molecules: Synthesis and Broad Absorption Bands

Abstract: Two donor-acceptor hybrid star-shaped D-pi-A molecules were facilely developed. The absorption spectra of TrTD2A and TrT2DA, which almost covered the whole visible range, were tuned by changing the ratio of donor and acceptor groups. However, the PL quantum efficiencies of TrTD2A and TrT2DA in solutions were dramatically reduced after the introduction of benzothiadiazole unit as acceptor chromophore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…[21] In this system, truxene acts as the core, connecting the D branch of the triphenylamine (TPA) unit and the A branch of the functionalized benzothiadiazole moiety. After the introduction of A groups, the absorption bands of the star-shaped molecules become broader and stronger in the range of 250 to 700 nm, which covers the whole visible region.…”
Section: Star-shaped Aromaticsmentioning
confidence: 99%
“…[21] In this system, truxene acts as the core, connecting the D branch of the triphenylamine (TPA) unit and the A branch of the functionalized benzothiadiazole moiety. After the introduction of A groups, the absorption bands of the star-shaped molecules become broader and stronger in the range of 250 to 700 nm, which covers the whole visible region.…”
Section: Star-shaped Aromaticsmentioning
confidence: 99%
“…Riobé et al have demonstrated that a 1,3,5‐triazine acceptor appended with two tetrathiafulvalene (TTF) donors has a lower‐energy charge‐transfer (CT) absorption band than the homologous mono‐appended system, EPR spectroscopy having demonstrated that the two TTF donors act independently of one another . Wang et al have reported unsymmetrical D–A motifs in which either one triarylamine (TAA) donor and two benzothiadiazole (BTD) acceptors, or vice versa, are appended to a truxene core . They demonstrated that increasing the acceptor character of the molecules broadens and intensifies the CT absorption bands in both solution and thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Dendrimer G0-2-1 was obtained in 64 % yield through a threefold WittigHorner reaction between trialdehyde 4 [15] and phosphonate 3. [18] Reduction of (E)-5-(2-(thiophen-2-yl)vinyl)thiophene-2-carbaldehyde with NaBH 4 gave 5 in 97 % yield.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%